The Optimal Structure of Technology Adoption and Creation: Basic Research vs. Development in the Presence of Distance to Frontier - Joonkyung Ha; Yong Jin Kim; Jong-Wha Lee (Asian Development Bank (ADB), 2009)
This paper presents a theoretical model and empirical evidence to explain the observation that a country in which the level of technology approaches the technology frontier tends to rely more on technology creation than adoption, and to invest more in basic research than in development. The model shows that technology creation involves both basic and development research processes while technology adoption uses only the latter process. Thus, research and development (R&D) investment in our model involves three different processes: basic research in technology creation, development in technology creation, and development in technology adoption. The results suggest first, that the rate of growth is positively correlated with the level of basic research activities in the technology creation sector, if one country's technology gap with the technology frontier is small enough. Second, an increase in the efficiency of the education system for highly skilled workers raises the level of basic research and the rate of growth. Third, verifying these theoretical results, empirical analyses using panel data of Japan; Republic of Korea; and Taipei,China show that the narrower the technological distance to the frontier, the higher the growth effect of basic R&D, indicating that the share of basic R&D matters for economic growth. Last, these also show that the quality of tertiary education has a significantly positive effect on the productivity of R&D.
hdl:11540/2566
Keywords: O31; O47; 330; Basic research; technology creation; technology adoption; economic growth; Technischer Fortschritt; Wirtschaftswachstum; Theorie